Medical negligence claims against Indian neurosurgeons and neurologists—A records review of National Consumer Dispute Redressal Commission (NCDRC) judgments - Aakash Ashishkumar Sethi; Gayatri Suvro Laha; Kalpita Samrat Shringarpure (Egyptian Journal of Neurosurgery)
Abstract Background As a specialty that frequently treats acute pathology and refractory pain, neurosurgery is at risk for medical negligence suits. In India, patients alleging medical negligence can seek compensation by approaching the “National Consumer Dispute Redressal Commission [NCDRC].” We aim to analyze NCDRC judgments against neurologists/surgeons based on the type of doctor (neurologist or neurosurgeon) implicated; neurological illnesses and interventions performed that frequently gave rise to negligence claims and the steps that the doctors can take to protect themselves. Methodology This is a retrospective records review. The judgments were accessed from https://www.scconline.com/ . Judgment’s body having the words “Medical,” “Negligence,” “neurosurgeon,” “neurosurgery,” etc., were included. Mann Whitney and chi-square test were used as tests of significance. Results Thirty-five judgments met the inclusion criteria. The majority of the cases were against neurosurgeons (23, 65%). The doctor’s specialty (neurosurgeon vs neurologist) (p = 0.28) had no bearing on the outcome of the case (doctor winning or losing). Significantly higher compensation was not awarded based on doctor’s specialty (U value = 20.5, p = 0.2). Spondylolisthesis (4, 11.4%) was the most common condition for which a patient was operated on by the neurosurgeon. Conclusion We found that the neurosurgeon was more commonly implicated in negligence cases as compared to neurologists. Meningioma and spondylolisthesis were the common Neurological illnesses that gave rise to negligence claims in India. Neurosurgeons can protect themselves by prompt postsurgical radiological tests when postoperative complications are suspected (Vijay Dutt v. Nagpal) and avoid expediting non-urgent surgeries solely at the request of the patient (Raj Hospital Vs Mahesh Varma).